KIRKPATRICK’S MODEL AS A FRAMEWORK FOR EVALUATING THE HEART ENLIGHTENMENT PROGRAM AT DARUL MUKHLISIN ISLAMIC BOARDING SCHOOL, PADANG LAMPE, UMI - Abdullah, Subhan; Mania, Sitti; Rasyid, Muhammad Nur Akbar (PT Altin Riset Publishing, 2025)
This study aims to evaluate the Heart Enlightenment Program implemented at Darul Mukhlisin Islamic Boarding School, Padang Lampe, using the Kirkpatrick evaluation model at Level 1 (Reaction) and Level 2 (Learning). The evaluation focuses on participants’ responses to the program and the changes in spiritual knowledge and understanding after participation. A qualitative research approach was employed, with data collected through in-depth interviews, participant observation, and document analysis. The participants consisted of 40 respondents, including students, boarding school administrators, mentors, and lecturers involved in the program. The findings at Level 1 show that most participants expressed positive reactions to the program, particularly regarding the relevance of the materials, the effectiveness of the instructional methods, the competence of the facilitators, and the supportive atmosphere for spiritual reflection. At Level 2, the results indicate that the program contributed significantly to enhancing participants’ understanding of Islamic values, self-discipline, and awareness of the importance of closeness to God as a foundation for daily life. Overall, the findings suggest that the Heart Enlightenment Program has been effective in strengthening students’ spiritual foundations and supporting the development of religious character within the campus environment. This study offers practical insights for improving the design and implementation of the Heart Enlightenment Program, particularly through strengthening instructional content, enhancing continuous monitoring, and ensuring the sustainability of the intended outcomes.